Pemilih Pemula dan Media Sosial: Menelusuri Faktor-Faktor Pembentuk Preferensi Politik - Angela, Sesdia; Nisaa, Fadhiilatun (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2025)
This study aims to investigate the factors influencing the political preferences of first-time voters (Gen Z) in the digital landscape, emphasizing the role of social media as a campaign tool and source of political information. A quantitative approach was adopted through a survey of 206 first-time voters in Pekanbaru. The collected data were statistically analyzed to identify correlations between the intensity of social media use, types of platforms, and shifts in political preferences. The findings reveal that social media is the primary source of political information (80% of respondents), with TikTok and Instagram being the most utilized platforms. Key factors influencing political preferences include (1) creativity in campaign content (55%), (2) responsiveness to current issues (40%), and (3) the impact of misinformation (30%). Candidates' vision and mission were the top consideration (85%), followed by experience (70%) and leadership qualities (65%). Approximately 30% of respondents changed their preferences after exposure to social media, while 70% maintained their initial choices due to emotional connections or shared values. This research significantly contributes to the understanding of digital political communication by illustrating the shift from traditional campaigns to visual content-based strategies. The findings also offer recommendations for the election commission and political parties to design data-driven campaigns.enhance voter media literacy, and address misinformation challenges. Theoretically, this study expands the concepts of digital political participation and selective exposure theory within the context of Indonesia's digital democracy.